PENGARUH DISIPLIN, MOTIVASI DAN PENGAWASAN TERHADAP KINERJA PEGAWAI PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH KABUPATEN DAIRI - Sianturi, Riny Priyanti; Lumban Gaol, Jonner; Sianturi, Marudut (JURNAL PROINTEGRITA, 2020)
Basically there are many factors affecting the performance variables of employees, but what is discussed in this study is limited to the factors of discipline, motivation and supervision because they are considered not optimal. This study aims at finding the effect of discipline, motivation and supervision simultaneously on employee performance in the Regional Financial and Asset Management Agency of Dairi Regency. The population of this research is 52 employees. In determining the number of samples, saturated samples are used so that the sample is 52 employees. The data collection techniques of this research are questionnaires, interviews and documentation study. While the data analysis techniques used are the classical assumption test, multiple regression, partial test, simultaneous test and the coefficient of determination. The results showed that the work discipline variable has a positive effect on employee performance at the Regional Financial and Asset Management Agency of Dairi Regency. The better the work discipline, the higher the performance. Work motivation variable has a positive effect on employee performance at the Regional Financial and Asset Management Agency of Dairi Regency. The better the work motivation, the higher the performance. Supervision variable has a positive effect on employee performance at the Regional Financial and Asset Management Agency of Dairi Regency. Simultaneously there is a significant influence of discipline, motivation, and supervision on employee performance. It is recommended that the leadership of the Dairi Regency Regional Financial and Asset Management Agency need to take stricter disciplinary action so that employees are always present on time during working hours, and actively monitor the implementation of their subordinates' work. It is necessary to consider adjusting the workload with the salary received by employees, as well as providing compensation for capacity building based on considerations of the employee's potential and performance. Leaders need to make better work measurements in order to accurately assess the level of achievement of organizational goals and to promote the achievement of work standards.